(untitled) (The Peerian Journal, 2026)
The researcher aims, through this study, to clarify the relationship between front office management and its impact on achieving organizational excellence through the mediation of artificial intelligence applications, and to identify the extent to which the dimensions of organizational excellence are implemented by the studied sample. The researcher began with a main problem that included several questions centered around the nature of the influential relationships between the studied variables. This was achieved by analyzing the opinions of the employees working in the front offices of Iraqi Airways, using (123) questionnaires distributed to front office management employees. The study aimed to determine the relationship and influence between front office management as an independent variable and artificial intelligence as a mediating variable, and their impact on organizational excellence as a dependent variable. The first variable included four dimensions (inquiries, reception, reservations, and cashier). The second variable included four dimensions (expert systems, neural networks, algorithms, and machine learning). The third variable included four dimensions (information technology, innovation, service quality, and motivation). These dimensions interacted with each other. In order to achieve the aforementioned study objective and answer the questions The research questions and hypothesis testing involved formulating several main and sub-hypotheses. The descriptive-analytical approach was adopted as the scientific methodology in this study to analyze the responses of the surveyed population. This was achieved through the use of a range of statistical measures and methods, including percentages, weighted arithmetic mean, standard deviation, relative importance, Z-test, F-test, coefficient of determination (R²), Spearman’s rank correlation coefficient, simple and multiple linear regression analysis, and confirmatory and exploratory factor analysis. The researcher concluded that the indirect influence of front office management on organizational excellence through artificial intelligence is significant.